Use of propolis in difficult to heal diabetic wounds. Short review - Chylińska-Wrzos, Patrycja; Lis-Sochocka, Marta; Jodłowska-Jędrych, Barbara (Polish Journal of Public Health, 2018)
According to WHO, about 347 million of people worldwide suffer from diabetes. Diabetes has complex etiology, and the consequences of this illness are seen in the morphological changes of many tissues and organs i.e. neuropathy leading to the risk of diabetic foot. Due to the diabetic condition, injuries to blood vessels in diabetic foot can be classified as chronic. This is because such wounds remain unresponsive to treatment for months or even years. There are many therapeutic methods employed in treating such injuries. These involve the use of silver, iodine or multi-antibiotic preparations, but treatment is expensive and cumbersome for patients. In the natural environment, however, there are many anti-inflammatory preparations, among them propolis which was the subject of our focus. Due to its anti-inflammatory, antimicrobial, and antioxidant properties, propolis is widely used in the treatment of colds, caries, rheumatic diseases, heart diseases and treatment of burns, wounds and frostbites. Nume -rous studies also indicate the beneficial effects of propolis on the difficult to heal diabetic wounds in which the use of propolis can significantly accelerate the healing process. The treatment utilizing propolis is easy, inexpensive and does not seem to cause any side effects, therefore costs can be reduced to minimum. The few studies conducted in diabetic patients confirm the results obtained in laboratory animals.